2021
DOI: 10.3389/fimmu.2021.699349
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Derived From the Lymphoid-Resident Commensal Bacteria Alcaligenes faecalis Functions as an Effective Nasal Adjuvant to Augment IgA Antibody and Th17 Cell Responses

Abstract: Alcaligenes spp., including A. faecalis, is a gram-negative facultative bacterium uniquely residing inside the Peyer’s patches. We previously showed that A. faecalis-derived lipopolysaccharides (Alcaligenes LPS) acts as a weak agonist of toll-like receptor 4 to activate dendritic cells and shows adjuvant activity by enhancing IgG and Th17 responses to systemic vaccination. Here, we examined the efficacy of Alcaligenes LPS as a nasal vaccine adjuvant. Nasal immunization with ovalbumin (OVA) plus Alcaligenes LPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…5b and Supplementary Fig. 4a ) 47 . Moreover, both CTA1-adjuvants effectively primed OT II CD4 T cells in the absence of cDC2DP cells in the huCD207/DTA mice (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…5b and Supplementary Fig. 4a ) 47 . Moreover, both CTA1-adjuvants effectively primed OT II CD4 T cells in the absence of cDC2DP cells in the huCD207/DTA mice (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Thus, the target population was restricted to cDC1 and did not depend on cDC2DP cells, despite that the latter carry CD103. In fact, huCD207DTU mice that were deficient in cCD2DP cells in mLN demonstrated full adjuvant and antigenic properties in response to the fusion protein, while Batf3−/−mice, lacking cDC1 cells, did not respond to CD103- or DD-targeting, but reacted to other adjuvants given intranasally 45 47 .…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that Alcaligenes LPS acts as an TLR4 agonist, thereby enhancing antigen-specific immune responses without excessive inflammation and leading to the possibility of its use as a safe adjuvant (Shibata et al, 2018;Wang et al, 2021). LPS is mainly composed of lipid A, core oligosaccharide, and O antigen among which lipid A is considered to be the active site of LPS and major determinant of LPS activity.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics prompted us to evaluate Alcaligenes-derived LPS and lipid A as a new and safe adjuvant candidate. Indeed, we found that both purified Alcaligenes LPS and chemically synthesized lipid A enhanced antibody production and Th17 responses to systemically or nasally immunized antigens (i.e., ovalbumin and pneumococcal surface protein A [PspA], a surface virulence factor of Streptococcus pneumoniae) (Wang et al, 2020;Yoshii et al, 2020;Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation